2020
DOI: 10.3390/w12072005
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Tradeoffs of Green to Grey Stormwater Infrastructure Using a Planning-Level Decision Support Tool

Abstract: Integrated decision support tools are needed to investigate the tradeoffs of stormwater control measures (SCMs) and determine the optimal suite of SCMs based on the needs of watersheds. In this study, an urbanized watershed undergoing infill development (the Berkeley neighborhood located in Denver, CO, USA) was modeled using a modified version of the U.S. Environmental Protection Agency’s (EPA) System for Urban Stormwater Treatment and Analysis IntegratioN (SUSTAIN). The primary goal was to compare the relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
(73 reference statements)
1
9
0
Order By: Relevance
“…The results are consistent with the research of Alves et al [93], Gallo et al [50], Bakhshipour et al [94], and Damodram et al [95]. Alves et al [93] applied MCDA methods to assess the flooding management in three study areas (Marbella, Ayutthaya, and Sukhumvit) and concluded that the green and grey combination measures provided more advantages compared with previously developed methods.…”
Section: Comprehensive Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The results are consistent with the research of Alves et al [93], Gallo et al [50], Bakhshipour et al [94], and Damodram et al [95]. Alves et al [93] applied MCDA methods to assess the flooding management in three study areas (Marbella, Ayutthaya, and Sukhumvit) and concluded that the green and grey combination measures provided more advantages compared with previously developed methods.…”
Section: Comprehensive Resultssupporting
confidence: 82%
“…Alves et al [93] applied MCDA methods to assess the flooding management in three study areas (Marbella, Ayutthaya, and Sukhumvit) and concluded that the green and grey combination measures provided more advantages compared with previously developed methods. Gallo et al [50] developed a modeling framework that encompasses green and grey stormwater facilities and was applied into the Berkeley neighborhood. They also reported that the optimal stormwater solution in the study area is a mix of green and grey combination.…”
Section: Comprehensive Resultsmentioning
confidence: 99%
“…The environmental benefits of SCP include improved hydrological performance (Dagenais et al, 2017;Spahr et al, 2020) such as stormwater quality improvement, flood mitigation, runoff reduction and groundwater recharge, as well as indirect benefits related to ecosystem services (Andersson et al, 2015;Dietrich and Rahul Yarlagadda, 2016;Gallo et al, 2020). Improved ecosystem services include adjustment to the local microclimate, carbon sequestration and storage, biodiversity conservation and restoration, and air pollution (Gómez-Baggethun and Barton, 2013;Ando and Netusil, 2018;Kazak et al, 2018).…”
Section: Environmental Benefitsmentioning
confidence: 99%
“…Urban drainage models usually aim at supporting decisions on flooding mitigation, pollution control, sewer system management and, increasingly, city planning and regeneration [1][2][3]. Depending on the objectives of the work and the availability of hydrological and asset data, the models can be either distributed and physically based or more aggregated and conceptual [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%